2017
DOI: 10.1080/15563650.2017.1401079
|View full text |Cite
|
Sign up to set email alerts
|

Fatal myocarditis and rhabdomyolysis induced by nivolumab during the treatment of type B3 thymoma

Abstract: Immune checkpoint inhibitors including programmed death-1 inhibitors are promising agents for many types of malignancies; however, it is still an off-label choice for type B3 thymoma. We reported for the first time a patient with type B3 thymoma developed fatal myocarditis and rhabdomyolysis after one dose of nivolumab administration. The results from myocardial and muscle biopsies revealed extensive myocyte damage, T-lymphocytic infiltration and strongly expression of PD-L1 which confirmed the nivolumab-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 10 publications
3
46
0
Order By: Relevance
“…The first specific report of myocarditis during treatment with a PD‐1/PD‐L1 inhibitor was published in 2014 [27], and a number of cases of ICI‐associated myocarditis have been described since . In an early analysis of more than 20,000 patients treated with ICIs, either alone or in combination, the incidence of myocarditis was 0.09%; the incidence of fatal myocarditis in this sample was 0.03% .…”
Section: Current Knowledgementioning
confidence: 75%
See 2 more Smart Citations
“…The first specific report of myocarditis during treatment with a PD‐1/PD‐L1 inhibitor was published in 2014 [27], and a number of cases of ICI‐associated myocarditis have been described since . In an early analysis of more than 20,000 patients treated with ICIs, either alone or in combination, the incidence of myocarditis was 0.09%; the incidence of fatal myocarditis in this sample was 0.03% .…”
Section: Current Knowledgementioning
confidence: 75%
“…There are no universally accepted criteria for a diagnosis of ICI‐associated myocarditis, but position statements and clinical practice guidelines for myocarditis due to other causes provide benchmarks. Inexpensive and widely available tests used for diagnosing ICI‐associated myocarditis include troponin measurements and electrocardiograms . However, these tests lack the sensitivity and specificity for a definitive myocarditis diagnosis.…”
Section: Current Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Based on results obtained in other solid, refractory tumors in adults, especially of squamous cell differentiation, and possibly considering PD-L1 expression observed in thymic epithelial tumor cellsdespite its intrinsic and constitutive relationship with the thymic origin of cancer cellsimmune checkpoint inhibitors of the PD-1/PD-L1 axis have been assessed in advanced and metastatic thymic epithelial tumors, mainly thymic carcinomas. Several case reports have been published, and four trials have assessed the efficacy and safety of PD-1/PD-L1 inhibitors in patients with advanced thymic epithelial tumors (Table 3) [48][49][50][51][52][53][54][55][56][57][58].…”
Section: Immunotherapy In Thymic Malignanciesmentioning
confidence: 99%
“…Outside of clinical trials, single case observations have been reported: a patient with type B2 thymoma treated with pembrolizumab who experienced severe mucocutaneous toxicity involving skin, mouth, esophagus, uvea and glands [48]; a patient with type B2 thymoma treated with a single dose of nivolumab who developed fatal myositis and myocarditis [58]; four patients who received nivolumab as second-or third-line treatment for PD-L1-positive thymic carcinoma with prolonged response or disease control [50]; and one patient with squamous cell thymic carcinoma who responded to pembrolizumab [49].…”
Section: Single Case Reportsmentioning
confidence: 99%